1995
DOI: 10.1351/pac199567071091
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimum epoxy/curing agent ratio: A study of different kinetic parameters

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Fraga et al (2008) reported that the bands at 1507 and 820 cm -1 could be assigned to the p-phenylene groups in the unreacted epoxide group. The disappearance of bands, as observed in the neat epoxy (ENC0), indicated that all of the epoxide groups reacted during curing and were well blended with the isophorone diamine curing agent (Nunez et al 1995;Fraga et al 2008). In the ENC nanocomposites, the epoxide group could react with the hydroxyl groups on the NC surfaces.…”
Section: Fourier Transform Infrared Spectroscopy Of Nanocellulose (Ncmentioning
confidence: 93%
“…Fraga et al (2008) reported that the bands at 1507 and 820 cm -1 could be assigned to the p-phenylene groups in the unreacted epoxide group. The disappearance of bands, as observed in the neat epoxy (ENC0), indicated that all of the epoxide groups reacted during curing and were well blended with the isophorone diamine curing agent (Nunez et al 1995;Fraga et al 2008). In the ENC nanocomposites, the epoxide group could react with the hydroxyl groups on the NC surfaces.…”
Section: Fourier Transform Infrared Spectroscopy Of Nanocellulose (Ncmentioning
confidence: 93%
“…An overall activation energy E a for the polymerization can also be obtained from t g of the curing process at isothermal T i ;25–27 as shown in eq 7, t i can be replaced with t g . The linear relationship of ln t g versus 1/ T i (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Errors originating from manual or automatic mixing are largely random in type and intensity and can impact the process significantly. Nunez et al [35] found that deviation in the curing agent ratio by just 1 part per hundred (phr) (from 34 to 35 phr) that was added to a DEGBA epoxy resin, lead to a decrease in the enthalpy of the reaction by $23 J/g and the glass transition temperature by 4 C. Decreases of these key properties in that range are operationally significant as they cause the decrease of curing rate due to reduced exothermic heat flux [36]. The study of Pandiyan Kuppusamy and Neogi [37] shows that the combined deviation of the catalyst and accelerator that were added into an ambient-curing polyester resin from 1 to 2 phr, results in an increase of the peak exotherm temperature by 8 C and an increase of the rate of temperature rise by 5.47 C/ min.…”
Section: Defects Induced By Mixingmentioning
confidence: 99%